Highly Efficient All-Solution-Processed Quantum Dot Light-Emitting Diodes Using MoOx Nanoparticle Hole Injection Layer - Ji-Hun Yang; Gyeong-Pil Jang; Su-Young Kim; Young-Bin Chae; Kyoung-Ho Lee; Dae-Gyu Moon; Chang-Kyo Kim (Nanomaterials, 2023)
This paper presents a study that aims to enhance the performance of quantum dot light-emitting didoes (QLEDs) by employing a solution-processed molybdenum oxide (MoOx) nanoparticle (NP) as a hole injection layer (HIL). The study investigates the impact of varying the concentrations of the MoOx NP layer on device characteristics and delves into the underlying mechanisms that contribute to the observed enhancements. Experimental techniques such as an X-ray diffraction and field-emission transmission electron microscopy were employed to confirm the formation of MoOx NPs during the synthesis process. Ultraviolet photoelectron spectroscopy was employed to analyze the electron structure of the QLEDs. Remarkable enhancements in device performance were achieved for the QLED by employing an 8 mg/mL concentration of MoOx nanoparticles. This configuration attains a maximum luminance of 69,240.7 cd/cm2, a maximum current efficiency of 56.0 cd/A, and a maximum external quantum efficiency (EQE) of 13.2%. The obtained results signify notable progress in comparison to those for QLED without HIL, and studies that utilize the widely used poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) HIL. They exhibit a remarkable enhancements of 59.5% and 26.4% in maximum current efficiency, respectively, as well as significant improvements of 42.7% and 20.0% in maximum EQE, respectively. This study opens up new possibilities for the selection of HIL and the fabrication of solution-processed QLEDs, contributing to the potential commercialization of these devices in the future.